2022
DOI: 10.3390/ijms23094558
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Resolution Structures and Mode of Action of Clinically Relevant Antimicrobial Peptides

Abstract: Global rise of infections and deaths caused by drug-resistant bacterial pathogens are among the unmet medical needs. In an age of drying pipeline of novel antibiotics to treat bacterial infections, antimicrobial peptides (AMPs) are proven to be valid therapeutics modalities. Direct in vivo applications of many AMPs could be challenging; however, works are demonstrating encouraging results for some of them. In this review article, we discussed 3-D structures of potent AMPs e.g., polymyxin, thanatin, MSI, proteg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 178 publications
0
12
0
Order By: Relevance
“…The cathelicidin family is one of the most important AMPs in the host immune defense system. So far, some of the cathelicidin-related drugs are undergoing clinical trials, indicating that cathelicidins have great potential to be developed as new antimicrobial drugs as alternatives to traditional antibiotics and medicines (Steinstraesser et al, 2011 ; Wang et al, 2019 ; Mookherjee et al, 2020 ; Díez-Aguilar et al, 2021 ; Bhattacharjya et al, 2022 ; Talapko et al, 2022 ). It has been reported that cathelicidins possess many important activities such as broad-spectrum and high antibacterial activity, anti-inflammation, and tissue damage inhibition (Auvynet and Rosenstein, 2009 ; Nijnik and Hancock, 2009 ; Wuerth and Hancock, 2011 ; Choi et al, 2012 ; Kahlenberg and Kaplan, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cathelicidin family is one of the most important AMPs in the host immune defense system. So far, some of the cathelicidin-related drugs are undergoing clinical trials, indicating that cathelicidins have great potential to be developed as new antimicrobial drugs as alternatives to traditional antibiotics and medicines (Steinstraesser et al, 2011 ; Wang et al, 2019 ; Mookherjee et al, 2020 ; Díez-Aguilar et al, 2021 ; Bhattacharjya et al, 2022 ; Talapko et al, 2022 ). It has been reported that cathelicidins possess many important activities such as broad-spectrum and high antibacterial activity, anti-inflammation, and tissue damage inhibition (Auvynet and Rosenstein, 2009 ; Nijnik and Hancock, 2009 ; Wuerth and Hancock, 2011 ; Choi et al, 2012 ; Kahlenberg and Kaplan, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous, circular dichroism (CD) studies showed that in the presence of a cell membrane-mimicking detergent, Intestinalin formed an α-helix ( 19 ). Therefore, we hypothesized that Intestinalin targets bacterial cell membranes similarly to other polycationic α-helical peptides ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that LTAs form a polyanionic ladder that helps cationic AMPs traverse the cell membrane of Gram-positive bacteria ( 35 ). In Gram-negatives, the role of LTAs is overtaken by lipopolysaccharide and outer membrane proteins that attract AMPs to the bacterial surface ( 21 ). That is probably the case with Intestinalin (P30), as the peptide is highly active against Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The lipopolysaccharide (LPS) outer membrane (or LPS-OM) of Gram-negative bacteria serves as a permeability barrier that limits intra-cellular access of several antibiotics [ 35 , 36 , 37 , 38 ]. Interactions of cationic AMPs with anionic phosphates of LPS or lipid A can cause an efficient permeabilization of the LPS-OM barrier [ 39 , 40 , 41 , 42 ]. AMP-mediated disruption of the LPS-OM is pivotal in killing Gram-negative bacteria [ 39 , 40 , 41 , 42 ].…”
Section: Antimicrobial Peptides (Amps) As Potential Alternatives To A...mentioning
confidence: 99%